Development of a thrombin generation test in cultured endothelial cells: Evaluation of the prothrombotic effects of antiphospholipid antibodies. Issue 169 (September 2018) - Billoir, Paul; Miranda, Sébastien; Damian, Louise; Richard, Vincent; Benhamou, Ygal; Le Cam Duchez, Véronique
Abstract: Introduction: Circulating antiphospholipid antibodies (APL) induce vascular injury and endothelial dysfunction, which are associated with thrombotic events and/or fetal loss. We developed a model in which calibrated automated thrombin generation (CAT) is carried out in wells lined with cultured endothelial cells. Then we investigated how far b2GP1 antibodies provoked thrombin generation (TG) enhancing effects in these cells and/or in blood platelets. Materials and methods: Thrombin generation induced by different concentrations of tissue factor and different levels of endothelial aortic cell confluence was investigated by calibrated automated thrombogram. Endothelial cells were incubated with the purified anti-β2glycoprotein I antibodies of patients with antiphospholipid syndrome (APS). Platelet free plasma and platelet rich plasma were used to study thrombin generation in endothelial cells and platelet reactivity, respectively. Results: Endothelial cell confluence was negatively correlated with thrombin generation which was dependent on the concentration of APL incubated. Activation of endothelial cells with APL significantly increased thrombin generation triggered by PFP. Triggering by PRP increased thrombinogram parameters. Moreover, anti-β2glycoprotein I antibodies incubated with platelet significantly amplified thrombin formation in PRP and induced platelet activation without tissue factor. Conclusion: In this in vitro study, we demonstrate the feasibility of using thrombin generation test in cultured endothelial cells and suggest the need to realize adjustments to standardize results. The mechanism of prothrombotic states in APS requires endothelial dysfunction and platelet activation. The quantification of thrombin formation shows that APL incubation induces endothelial injury in cultured cells amplified by platelets. Highlights: Thrombin generation is realizable in cultured endothelial cells. When endothelial cells are incubated with APL thrombin generation is increased. When platelets are incubated with APL thrombin generation is increased in EC. APL had the capacity to induce direct platelet activation.